Characterization of the whole chloroplast genome Caulerpa lentillifera J. Agardh (Bryopsidales, Chlorophyta) - Gao, Dahai (Mitochondrial DNA B Resour, 2018)
The whole chloroplast genome (cp DNA) sequence of Caulerpa lentillifera J. Agardh has been characterized from Illumina pair-end sequencing. The circular cpDNA was 119,402 bp in length, containing 122 genes, which included 91 protein-coding genes, 28 tRNA genes, and 3 ribosomal RNA genes (four rRNA species). The overall AT content of C. lentillifera cpDNA is 67.4%. The 48 genes phylogenetic analysis suggested that C. lentillifera formed a monophyletic clade with congeneric C. racemosa.